Criopreservação e técnicas de intercâmbio de embriões zigóticos de acessos de coqueiro - Oliveira, Leila Albuquerque Resende de (2015)
The objective of this study was to evaluate the effect of cryoprotectant solutions, immersion times and regeneration means of zygotic embryos cryopreserved coconut and evaluate the effect of different procedures for packaging and storage time on contamination and germination of zygotic embryos. For cryopreservation were used zygotic embryos obtained from mature fruits of Brazil Green Dwarf (BGD) and Brazilian Tall (BRA) accessions of Active Bank Coconut Germplasm Embrapa Coastal Tablelands. BGD coconut seeds were placed in two cryoprotectant solutions: C1 - medium Y3 + 1.75 M sucrose + 15% glycerol, C2 - medium Y3 + 3.33 M glucose + 15% glycerol and BRA coconut embryos in solutions: C1 - medium Y3 + 3.33 M glucose and C2 - medium Y3 + 3.33 M glucose + glycerol 15%, both accesses remained immersed for 24, 48 and 72 hours. Thereafter explants were dehydrated on silica gel 34 (BGD) and 30 hours (BRA) and immersed in liquid nitrogen at - 196 ° C for 24 hours, after this period were thawed at 38 ± 2 ° C. It was determined the humidity of the embryos at the end of step of cryoprotectants and dehydration treatments. The percentage of survival and regeneration was assessed after the embryo transfer into the culture medium Y3 supplemented or not with mol 0.5 gibberellic acid. The pre-cultivation in cryoprotectant solutions and different immersion times did not affect embryo viability. The cryoprotective solution composed of 1.75 M sucrose and 15% glycerol showed lower moisture content (12.3%) and improved survival (63.3%) to the coconut BGD zygotic embryos cryopreserved. The BRA access the embryos reached 77.8% survival when immersed in cryoprotectant formed medium Y3 + 3.33 M glucose, however, both cryoprotectant solutions when combined with the shortest time of immersion (24 hours) may be recommended. For studies of transport and storage procedures were used Cameroon red dwarf (CRD), Malayan yellow dwarf (MYD) and Malayan red dwarf (MRD) acessions. We evaluated five cases; T1 endosperm disk storage at 10 ± 2 ° C for 5 days; T2 endosperm disk storage at 10 ± 2 ° C for 8 days; T3 endosperm disk storage at 10 ± 2 ° C for 12 days (before excision and embryo inoculation in culture medium Y3); T4 excised zygotic embryo and inoculated into culture medium Y3 in individual storage and 5 ml microtube 2 days and then transferred to culture medium Y3; T5- five zygotic embryos inoculated in culture medium Y3 in a Petri dish after 2 days and transferred to culture medium Y3. The transport zygotic embryos in Petri plate with Y3 culture medium without sucrose for two days promotes low percentage of bacterial contamination. All procedures studied promote low fungal contamination. The transport endosperm discs in plastic bags and stored for five, eight, and twelve days promotes higher germination of zygotic embryos uncontaminated MRD and MYD access. The transport of isolated zygotic embryos in microtube with Y3 culture medium without sucrose for two days and endosperm discs in plastic bags and stored for five and eight days promote increased germination of zygotic embryos uncontaminated CRD access.